Oligonol®, an oligomerized polyphenol from Litchi chinensis extract, enhances cisplatin sensitivity and inhibits invasion in bladder cancer cells by the TNF-α/NF-κB/Snail pathway - Yu-Chi Chen; Hung-Yu Lin; Sue-Joan Chang; Ching-Yu Huang; Yun-Ching Chang (CyTA - Journal of Food)
Oligonol® (Olg) is an oligomerized polyphenol with a higher bioavailability and exhibits excellent antioxidant and anti-inflammatory properties. However, the effects and underlying mechanisms of Olg on bladder cancer are still largely unknown. The current study found that Olg markedly reduced the viability of bladder cancer cells through the induction of caspase-dependent apoptosis while exhibiting no noticeable toxicity to normal bladder cells. Combining Olg and cisplatin resulted in a synergistic cytotoxic effect on bladder cancer cells. Olg also inhibited cell migration and invasion by affecting the expression of E-cadherin, Snail, N-cadherin, and vimentin. These effects of Olg were significantly weaker in the NF-κB silencing cells, revealing that Olg may inhibit cell viability and motility by modulation of the TNF-α/NF-κB/Snail pathway in human bladder cancer cells. Olg acts against cancer cells and enhances cisplatin chemotherapy, and it holds great potential as an anticancer drug or complementary medicine for bladder cancer.